1994
DOI: 10.1111/j.1365-2141.1994.tb05064.x
|View full text |Cite
|
Sign up to set email alerts
|

Haemopoiesis of transplanted patients with autologous marrows assessed by long‐term marrow culture

Abstract: We assessed the effect of antitumoural therapy at intensive doses on the haemopoietic system using long-term marrow cultures (LTMC) established from 33 patients (25 with haematological diseases and eight with solid tumours) after autologous bone marrow transplantation (ABMT). When compared to 42 pre-graft patients, a decreased CFU-GM production and a defect in stromal layer (SL) confluence were found after ABMT on day 90 but also on day 365. However, these abnormalities were observed only in patients with haem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…5,6,21 It is already well known that there is a correlation between the number of cycles of radio/chemotherapy and depletion of the stem cell compartment. 1 On the other hand, the reports of reversible changes after transplantation 20 have all been observed in patients transplanted with allogeneic bone marrow for acute leukaemia and aplastic anemia (in both cases with relatively short courses of chemotherapy).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6,21 It is already well known that there is a correlation between the number of cycles of radio/chemotherapy and depletion of the stem cell compartment. 1 On the other hand, the reports of reversible changes after transplantation 20 have all been observed in patients transplanted with allogeneic bone marrow for acute leukaemia and aplastic anemia (in both cases with relatively short courses of chemotherapy).…”
Section: Discussionmentioning
confidence: 99%
“…A large number of authors have found a decrease in colony-forming unit (CFU-C) levels in both allogeneic and autologous bone marrow recipients (ABMT) a long time after transplant (up to 8.5 years). 4,5 Domenech et al 6 found an impairment in the long-term cultures of 33 patients after autologous bone marrow transplantation: the defect involved both CFU-C output and stromal cell formation. Using different techniques, van den Berg et al 7 and O'Flaherty et al 8 clearly demonstrated that a stromal cell compartment defect is always present after allogeneic bone marrow transplantation.…”
mentioning
confidence: 99%
“…Various studies to date have evaluated the toxic effects of HDC and demonstrated severe and irreversible damage on mature bone marrow stromal compartments in vivo and in vitro [5][6][7][8][9][10][11][12][13][14]. These effects are relevant not only in patients treated with HDC without allogeneic stem cells but also in recipients of allogeneic stem cell transplants in whom bone marrow stroma remains recipient in origin after the transplant [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also demonstrated that a recipients stromal cells are damaged after bone marrow transplantation [6][7][8], or even from chemotherapeutic drugs alone [6][7][8][9][10][11][12][13][14][15]. We have also recently demonstrated a significant reduction in MSC expansion and MSC CD44 expression by MSCs derived from patients receiving HDC regimens for hematological malignancies, thus implicating potential disadvantages in the use of autologous MSCs in chemotherapeutically pre-treated patients for future therapeutic strategies [16].…”
Section: Introductionmentioning
confidence: 99%